Pengaruh Lingkungan kerja, Kepuasan kerja dan Beban kerja terhadap Kinerja Karyawan (Departemen Sewing PT. TPINC JAKARTA) - Khafid, Abdul; Khoirunisa, Nadhia (Jurnal Doktor Manajemen (JDM), 2025)
The aim of this research is to  determine the influence of the Work Environment, Job Satisfaction and Workload on Employee Performance. This study uses a quantitative approach with a survey method. Data collection was carried out through a questionnaire. The population in this study was 125 people, namely all employees who work specifically in the Sewing Department, while the sampling method used the Slovin method, with a sample of 95 people. Data analysis used multiple linear regression methods. The results of the analysis showed that partially the variables of Work Environment (significance 004), Job Satisfaction (significance 000) and Workload (significance 001) had a positive and significant effect on Employee Performance. Simultaneously, the three variables had a significant effect with an Fcount value of 17.207> Ftable 2.70 and a significance of 0.000. The coefficient of determination (R2) of 36.2% explains that the influence of the independent variables is quite representative of some variations in employee performance, while the rest is influenced by other variables. The company management is expected to focus on strategies to improve these three aspects in order to increase employee productivity and performance.